Heated air humidification versus cold air nebulization in newly tracheostomized patients - Birk, Richard; Schell, Angela; Kramer, Benedikt; Aderhold, Marc Christoph; Hörmann, Karl; Sommer, Ulrich (Head & neck, 2017)
Background After tracheostomy, the airway lacks an essential mechanism for warming and humidifying the inspired air with the consequent functional impairment and discomfort. The purpose of this study was to compare airway hydration with cold-air nebulization versus heated high-flow humidification on medical interventions and tracheal ciliary beat frequency (CBF). Methods Newly tracheostomized patients (n = 20) were treated either with cold-air nebulization or heated humidification. The number of required tracheal suctioning procedures to clean the trachea and tracheal CBF were assessed. Results The number of required suctions per day was significantly lower in the heated humidification group with medians 3 versus 5 times per day. Mean CBF was significantly higher in the heated humidification group (6.36 ± 1.49 Hz) compared to the cold-air nebulization group (3.99 ± 1.39 Hz). Conclusion The data suggest that heated humidification enhanced mucociliary transport leading to a reduced number of required suctioning procedures in the trachea, which may improve postoperative patient care.